Exploring Leadership Based on Local Wisdom: Leadership Learning in Pesantren - Najiburrahman, Najiburrahman; Wahid, Abd Hamid; Khoir, Muhammad Ilzam; Hefniy, Hefniy; Mudarris, Badrul (JURNAL ISLAM NUSANTARA, 2024)
This study explores local wisdom-based leadership in Islamic boarding schools, using the Suchman Inquiry model as a leadership learning model. This study uses a qualitative approach with a case study. Data collection in this study was carried out circularly using three approaches: l) observation, 2) in-depth interviews, and 3) documentation. Document data analysis was carried out by collecting, selecting, and grouping data, then concluding without eliminating the original value of the data. The results of this study can be used as a basis for developing a local wisdom-based leadership curriculum in Islamic boarding schools. Integrating local values identified through the Suchman Inquiry model will make the curriculum more relevant and contextual for students.